2015
DOI: 10.1097/ajp.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Dose of Naloxone as an Adjuvant to Intrathecal Morphine Infusion Improves Perceived Quality of Sleep but Fails to Alter Persistent Pain

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
17
1
Order By: Relevance
“…One trial, with risk of bias relating to blinding and incomplete outcome data, evaluated intravenous calcitonin for phantom limb pain in 20 patients, and found no effect up to 48 h after infusion compared with saline. Another trial, with no clear evidence of risk of bias, evaluated low doses of oral/or intravenous naloxone as a supplement in 12 patients whose severe CPSP was already managed by continuous intrathecal morphine administration. No evidence of an effect on pain relief was found after two 3‐week sessions on differing doses of the drug across a 9‐week period…”
Section: Resultsmentioning
confidence: 99%
“…One trial, with risk of bias relating to blinding and incomplete outcome data, evaluated intravenous calcitonin for phantom limb pain in 20 patients, and found no effect up to 48 h after infusion compared with saline. Another trial, with no clear evidence of risk of bias, evaluated low doses of oral/or intravenous naloxone as a supplement in 12 patients whose severe CPSP was already managed by continuous intrathecal morphine administration. No evidence of an effect on pain relief was found after two 3‐week sessions on differing doses of the drug across a 9‐week period…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, sleep deprivation decreases morphine analgesia, possibly by decreasing descending pain inhibitory activity and by increasing descending pain facilitatory activity [97]. Conversely, sleep improves from intrathecal morphine infusion in patients with severe pain [98]. A recent meta-analysis showed that sleep disturbance is associated with increase in markers of systemic inflammation [99].…”
Section: Discussionmentioning
confidence: 97%
“…Our group performed a pilot study consisting of eleven patients with persistent pain following multiple surgeries, who were being treated with continuous intrathecal morphine administration; in the study, ultralow-dose naloxone was administered via the same route [118]. The reason for not using the above discussed triple combination is that we wanted the option to investigate the effect of each agent individually in vivo.…”
Section: Clinical Applicationsmentioning
confidence: 99%